Embodied Rationality Through Game Theoretic Glasses: An Empirical Point of Contact - Lerique, Sébastien (Frontiers in Psychology, 2022)
The conceptual foundations, features, and scope of the notion of rationality are increasingly being affected by developments in embodied cognitive science. This paper starts from the idea of embodied rationality, and aims to develop a frame in which a debate with the classical, possibly bounded, notion of rationality-as-consistency can take place. To this end I develop a game theoretic description of a real time interaction setup in which participants' behaviours can be used to compare the enactive approach, which underlies embodied rationality, with game theoretic approaches to human interaction. The Perceptual Crossing Paradigm is a minimal interaction interface where two participants each control an avatar on a shared virtual line, and are tasked with cooperatively finding each other among distractor objects. It is well known that the best performance on this task is obtained when both participants let their movements coordinate with the objects they encounter, which they do without any prior knowledge of efficient interaction strategies in the system. A game theoretic model of this paradigm shows that this task can be described as an Assurance game, which allows for comparing game theoretical approaches and the enactive approach on two main fronts. First, accounting for the ability of participants to interactively solve the Assurance game; second, accounting for the evolution of choice landscapes resulting from evolving normative realms in the task. Similarly to the series of paradoxes which have fuelled debates in economics in the past century, this analysis aims to serve as an interpretation testbed which can fuel the current debate on rationality.